2001
DOI: 10.1046/j.1365-2141.2001.02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Microangiopathic haemolytic anaemia in metastasizing malignant tumours is not associated with a severe deficiency of the von Willebrand factor‐cleaving protease

Abstract: Summary. Complete deficiency of von Willebrand factorcleaving protease (VWF-cp) has recently been identified as a pathogenetically important factor for thrombotic thrombocytopenic purpura (TTP). Microangiopathic haemolytic anaemia (MAHA) with thrombocytopenia in patients with metastasizing neoplasms is clinically similar to TTP, however, the pathogenesis of the condition is unclear. Partial deficiency of VWF-cp in metastasizing malignancy has recently been reported in patients without MAHA. Our study shows nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 12 publications
6
54
1
3
Order By: Relevance
“…Nevertheless, it is also evident from our study that slightly decreased (25%-50%) or moderately decreased ADAMTS13 activity (10%-25%) is rather common in thrombocytopenic patients with severe sepsis or HIT, a finding that is compatible with the observation of mild ADAMTS13 deficiency in various inflammatory disease states 17 and in patients with metastasizing neoplasia 20 or neoplasia-associated thrombotic microangiopathy. 21 Even though very low ADAMTS13 activity (Ͻ 5% of the activity in NHP) is a specific feature of the clinical condition labeled TTP, the sensitivity of this laboratory finding for the diagnosis of TTP remains questionable. Although, in retrospective studies, Tsai and Lian 5 observed severe ADAMTS13 deficiency in 37 of 37 patients and Furlan et al 4 in 26 of 30 patients with a diagnosis of acute TTP, the prospective study by Veyradier et al 7 found a severe deficiency in only 47 of 66 patients presenting with idiopathic or secondary TTP (sensitivity, 71%).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is also evident from our study that slightly decreased (25%-50%) or moderately decreased ADAMTS13 activity (10%-25%) is rather common in thrombocytopenic patients with severe sepsis or HIT, a finding that is compatible with the observation of mild ADAMTS13 deficiency in various inflammatory disease states 17 and in patients with metastasizing neoplasia 20 or neoplasia-associated thrombotic microangiopathy. 21 Even though very low ADAMTS13 activity (Ͻ 5% of the activity in NHP) is a specific feature of the clinical condition labeled TTP, the sensitivity of this laboratory finding for the diagnosis of TTP remains questionable. Although, in retrospective studies, Tsai and Lian 5 observed severe ADAMTS13 deficiency in 37 of 37 patients and Furlan et al 4 in 26 of 30 patients with a diagnosis of acute TTP, the prospective study by Veyradier et al 7 found a severe deficiency in only 47 of 66 patients presenting with idiopathic or secondary TTP (sensitivity, 71%).…”
Section: Resultsmentioning
confidence: 99%
“…Abbreviations: ADAMTS13, a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13; TMA, thrombotic microangiopathy. measurable in most cases [24,25], suggesting that ADAMTS13 dysfunction is not the prominent abnormality involved in cancer-associated TMA pathophysiology. A mild to moderate decrease in ADAMTS13 activity was observed in four cases.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that VWF-cleaving protease deficiency is specific for TTP has also been challenged by Oleksowicz et al, 24 who found a severe deficiency of the protease in patients with metastatic malignancies in the absence of TTP, even though others have found normal or slightly reduced protease levels in similar patients. 25 Our study, carried out in a broad inclusive population of healthy controls from newborns to elderly and in several physiologic inflammatory and disease states, demonstrates that the protease is low or very low in an array of clinical conditions unrelated to TTP, even though it was completely unmeasurable only in the 2 patients with chronic relapsing TTP.…”
Section: Discussionmentioning
confidence: 99%